Lipid interconversions in aging Mycoplasma capricolum cultures. - Gross, Z (1986)
During the progression of Mycoplasma capricolum cultures from the early exponential to the stationary phase of growth, a decrease in the phospholipid-to-protein ratio and increases in both the unsaturated-to-saturated fatty acid ratio and the diphosphatidylglycerol (DPG)-to-phosphatidylglycerol (PG) ratio were found. The freedom of motion of spin-labeled fatty acids incorporated into the membrane remained unchanged throughout the growth cycle. The increase in DPG was almost stoichiometric with the decrease in PG. Furthermore, exogenous PG added to the medium was incorporated by the cells and partially converted to DPG. The DPG that was accumulated upon aging was always more unsaturated than the PG. This accumulation was enhanced in palmitic acid-poor media, but was inhibited even in aged cells when the cells were grown in palmitic acid-rich media, suggesting that the accumulation of DPG upon aging was associated with changes in the fatty acid composition of membrane lipids rather than with the transition of the cells from the exponential- to stationary-growth phase.